Transformation of fresh yams (Dioscorea trifida) into flours and starches: sustainable options for the food industry contributing to the development of this production chain - Maria Cristina Ferrari; Roseli Aparecida Ferrari (Scientia Agricola)
ABSTRACT Despite the significant socioeconomic impact of yam cultivation in developing countries, this field needs more scientific studies and incentives. In Brazil, the absence of a developed processing chain has resulted in a considerable production loss due to the predominant form of commercialization (in natura). This study aimed was to examine the physicochemical and technological composition of yams of the species Dioscorea trifida L., including both white and purple varieties. The aim was to contribute to an increase in food utilization and technological potential. The proximate composition of the flours indicated that the yam species investigated have the potential for human consumption and are good sources of energy (1,489 and 1,527 kJ), with considerable levels of total fiber (8.18 and 6.69 g 100 g–1), potassium (1,325 and 981 mg 100 g–1), and phenolic compounds (133 and 110 mg 100 g–1) for white and purple yams, respectively. Additionally, the yams demonstrated distinct properties in water and oil, indicating their potential for use in breading applications. The viscoamylographic profiles of purple yam flour and yam starches were found suitable for use in quick-cooking foods that reach high viscosity when heated, whereas white yam flour was identified as a suitable thickening agent. The yams yielded flours and starches with favorable characteristics as food ingredients, offering greater added value and enhanced stability compared to the original raw materials. They present a sustainable alternative for reducing post-harvest losses and, as they are gluten-free, they cater to the celiac population.